Two cases of acute pulmonary artery embolism triggered by fresh and chronic mixed‐vein thrombosis with a "Blowfish sign". Issue 4 (17th March 2023) - Tsubouchi, Hiromasa; Onishi, Hidenori; Maeno, Koji; Hayashi, Hiroyuki; Yamamura, Osamu
Abstract : Ultrasonography and computed tomography of the lower extremities revealed fresh and chronic mixed‐vein thrombosis (FCMVTs) presenting the "Blowfish sign, " accompanied by pulmonary embolism. FCMVTs presenting the "Blowfish sign" may increase the risk of fatal pulmonary embolism, and its detection by ultrasonography is important for preventing pulmonary embolism.